Konsep Pendidikan Karakter KH Ahmad Dahlan Dalam Perspektif Tokoh Muhammadiyah - Wiranata, Rz. Ricky Satria (?ALI?A, 2019)
This research aimed to know about brain concept of KH. Ahmad Dahlan as comprehensive for a perspective of Muhammadiyah about character education concept. By this research hope can increasing new knowledge and can be a reference for a need education practice and then a character education concept.